Addressing gender inequalities and strengthening women's agency to create more climate-resilient and sustainable food systems - Bryan, Elizabeth; Alvi, Muzna; Huyer, Sophia; Ringler, Claudia (Elsevier, 2024)
Climate change affects every aspect of the food system, including all nodes along agri-food value chains from production to consumption, the food environments in which people live, and outcomes, such as diets and livelihoods. Men and women often have specific roles and responsibilities within food systems, yet structural inequalities (formal and informal) limit women's access to resources, services, and agency. These inequalities affect the ways in which men and women experience and are affected by climate change. In addition to gender, other social factors are at play, such as age, education, marital status, and health and economic conditions. To date, most climate change policies, investments, and interventions do not adequately integrate gender. If climate-smart and climate-resilient interventions do not adequately take gender differences into account, they might exacerbate gender inequalities in food systems by, for instance, increasing women's labor burden and time poverty, reducing their access to and control over income and assets, and reducing their decision-making power. At the same time, women's contributions are critical to make food systems more resilient to the negative impacts of climate change, given their specialized knowledge, skills and roles in agri-food systems, within the household, at work and in their communities. Increasing the resilience of food systems requires going beyond addressing gendered vulnerabilities to climate change to create an enabling environment that supports gender equality and women's empowerment, by removing structural barriers and rigid gender norms, and building equal power dynamics, as part of a process of gender transformative change. For this to happen, more research is needed to prioritize structural barriers that need to be removed and to identify effective gender transformative approaches.